Analysis of Torque Maintenance and Fracture Resistance after Fatigue in Retention Screws Made of Different Metals for Screw-Retained Implant-Borne Prosthesis Joints - Bello Taborda, Maria Beatriz [UNESP]; Yaguinuma Goncalves, Gabriela Sumie [UNESP]; Alves De Sousa, Cecilia [UNESP]; Goncalves Assuncao, Wirley [UNESP] (Hindawi, 2021)
Purpose. The aim was to evaluate the effect of different metallic alloys used in the manufacture of retention screws for universal cast to long abutment (UCLA) abutments for external hexagon (HE) and Morse taper (MT) connection implants, as well as of mechanical cycling on torque maintenance and fracture resistance through electromechanical fatigue testing by mastication followed by compression testing. Methods. Sixty implants were used, 30 MT and 30 HE, with their respective titanium UCLA abutments and retention screws of 5 different materials (n = 6): Ti cp grade 2, Ti cp grade 4, Ti cp grade 4 hard, Ti grade 5 - Ti6Al4V and surgical steel (DSP® Biomedical). The assemblies were positioned in an electromechanical masticatory fatigue testing machine. The fracture strength test was performed by compression testing in a universal testing machine EMICDL-200. Results. The cycled screws and new screws of each alloy group for each connection type were evaluated, obtaining the maximum force (FM), in order to verify the effect of mechanical cycling. The data were tabulated and submitted to appropriate statistical analysis (α = 0.05). Conclusion. It was concluded that for the MT, the alloy with the best performance was steel, both in the maintenance of torque and in the compression test, and cycling negatively influenced the maintenance of preload for this connection. The alloy material did not influence torque maintenance for HE. The new screws that were subjected to EMIC showed higher strength. The alloy with the lowest strength was Ti grade 2.